2018
DOI: 10.1089/end.2017.0761
|View full text |Cite
|
Sign up to set email alerts
|

Is the Preoperative Level of Procalcitonin a Valid Indicator for Predicting Postoperative Fever After Percutaneous Nephrolithotomy?

Abstract: We concluded that patients with preoperative fever, stone burden >353 mm, PCT >0.05 ng/mL, or positive urine culture were more likely to develop postoperative fever and that routinely detecting PCT levels before PNL would be helpful in predicting postoperative fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Besides, for patients with hydronephrosis before surgery, sometimes due to urinary tract obstruction is more serious, after antibiotic treatment, urinary leukopenia. And there may be an illusion that preoperative infection is basically controlled, but the renal pelvis fluid is still turbid and even purulent, and the bacteria in the stones still remain (3,16). Therefore, we believe that patients with preoperative urinary tract infection should be given sufficient attentions, adequate active treatment with sensitive antibiotics to reduce postoperative infection are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, for patients with hydronephrosis before surgery, sometimes due to urinary tract obstruction is more serious, after antibiotic treatment, urinary leukopenia. And there may be an illusion that preoperative infection is basically controlled, but the renal pelvis fluid is still turbid and even purulent, and the bacteria in the stones still remain (3,16). Therefore, we believe that patients with preoperative urinary tract infection should be given sufficient attentions, adequate active treatment with sensitive antibiotics to reduce postoperative infection are needed.…”
Section: Discussionmentioning
confidence: 99%
“…As a common urological disease, the incidence of urinary tract calculi has significantly increased in recent years, if left untreated, it can severely impair the function of urinary system (1,2). Percutaneous nephrolithotomy (PCNL) has gradually become the preferred choice for the treatment of urinary calculi clinically, and its safety and efficacy have been recognized by patients and clinician (3). However, PCNL can complicate many adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that positive UC was the independent risk factor for postoperative infectious complications [2]. Procalcitonin (PCT) is a biomarker for the diagnosis of sepsis and prognosis of bacterial infections whose high levels appeared strongly correlated with systemic bacterial infections [3,4]. However, many clinicians believe that serum PCT is not sufficiently specific or sensitive to GP bacteria and some studies reported that PCT is higher in Gramnegative bacteremia than Gram-positive bacteremia and fungemia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The present study has found that the postoperative serum levels of IL-6 was significantly lower in patients with urosepsis of the EXP group in comparison with those in the CON group, which represented an alleviated severity of infection and inflammation. PCT, as a 116-amino acid polypeptide, is secreted from neutrophils and parenchymal cells when bacterial infections occur and is a valuable biomarker for early diagnosis of systemic infection, especially for sepsis, and PCT can be up-regulated by bacterial endotoxins and proinflammatory mediators such as IL-6 and tumor necrosis factors and will be down-regulated when infection is controlled, and the concentrations of endotoxins and proinflammatory mediators decreas [28][29][30][31]. The value of PCT can represent the severity of infection.…”
Section: Discussionmentioning
confidence: 99%